ANALISIS TINGKAT KEPUASAN MASYARAKAT TENTANG LAYANAN SERTIFIKASI HALAL DI KABUPATEN SUMBAWA - Roos Nana Sucihati; Dedy Heriwibowo; Andi Kusmayadi (Jurnal Ekonomi & Bisnis, 2023)
This study aims to determine the level of community satisfaction regarding halal certification services in Sumbawa Regency. This research uses a quantitative descriptive approach. The type of data used in this study is quantitative data obtained directly from primary sources using a questionnaire as an instrument for data collection. To obtain an overview of the level of public satisfaction with the performance of halal certification services organized by the Halal Center of Sumbawa Regency, a simple approach was used referring to the Minister of Administrative and Bureaucratic Regulation Number 14 of 2017 concerning measuring the index of public satisfaction with public services. Based on the results of the research that has been carried out, it is concluded that the implementation of halal certification services at the Halal Center of Sumbawa Regency generally reflects a good level of quality. The average value of SMEs after conversion is 86.53 and is in the Good Category. This means that the Halal Center of Sumbawa Regency has served halal certificate applicants well, although there are several aspects that still require improvement. The service element that received the highest assessment from respondents was the behavior of service implementers, while the service element that received the lowest assessment from respondents was the availability of service facilities and infrastructure.